Intensitas Penggunaan Media Sosial Dapat Mempengaruhi Terjadinya Insomnia Pada Remaja Di SLB N 2 Yogyakarta - Cahyani Cahyani, Margareta; Riyadi, Sujono (Jurnal Indonesia Sehat, 2023)
Background: Insomnia is the inability to meet the need for sleep, a condition experienced by people who experience chronic sleep difficulties, frequent awakenings from sleep, and short sleep. One of the causes of insomnia is the duration of using social media for a long time. Social media that are widely used today are Facebook, Whatsapp, Instagram, and Tik-tok. The purpose of this study was to see a relationship between the intensity of social media use and the incidence of insomnia in adolescents at SLB N 2 Yogyakarta Methods: This research is a type of quantitative research. The design of the study used correlation (correlation study) with a cross-sectional approach. For taking this sample, using the total sampling technique, the students of SMP and SMA SLB Negeri 2 Yogyakarta. Using somers'd statistical test. Results: In this study, the results were p = 0.020 and r = 0.521. There is a relationship between the intensity of social media use and the incidence of insomnia in adolescents at SLB Negeri 2 Yogyakarta. Conclusions: There is a significant relationship between the use of social media and the incidence of insomnia in adolescents at SLB Negeri 2 Yogyakarta.